Living Nonviolently : Language for Resisting Violence. - Moran, Gabriel (Rowman & Littlefield Pub. Group, 2011)
Are human beings naturally violent? Is war the fate of the human race? Despite the depressing record of the past, the world's future depends upon avoiding war and drastically reducing violence. Living Nonviolently: Language for Resisting Violence examines carefully the language of violence and war. One of the first casualties of violence is language, which in turn makes resistance to violence difficult to articulate. In the first four chapters, Gabriel Moran proposes distinctions for the interconnected ideas of force, power, aggressiveness, violence and war--not to invent a new and logical la.